Actions for Arctic Biodiversity 2013-2021, Progress report 2017-2019 - Conservation of Arctic Flora and Fauna (CAFF) (Arctic Council Secretariat, 2019)
Progress report 2017-2019. The Actions for Arctic Biodiversity, 2013-2021 (Action Plan) comprises the implementation plan for the recommendations from the Arctic Biodiversity Assessment (ABA). It is a living document that is reviewed and updated every two years. The plan is not meant to be exhaustive or to replace working group work plans; rather it is complimentary, emphasizing specific actions that address ABA recommendations.